The development of image capturing system and information system for craniofacial reconstruction - Setan, Halim; Majid, Zulkepli; Suwardi, Deni (2004)
A multi-disciplinary research is established between Universiti Teknologi Malaysia (UTM), Standards & Industrial Research Institute Malaysia (SIRIM), and Universiti Sains Malaysia (USM). The research focuses on the development of surgical planning system for craniofacial reconstruction, for both the soft and hard tissues. This paper discusses the research works undertaken by UTM, especially on the development of a close range image capturing system and information system for craniofacial. The image capturing system combines the laser scanning and photogrammetric techniques for acquiring high-resolution 3D models of craniofacial soft tissue. The resulted 3D models are processed and combined with other relevant data (such as hard tissue, measurement, and patient’s information) for the development of nation-wide database for normal and malformation craniofacial. The information system is used for managing and visualizing the craniofacial data. Preliminary results are also included to highlight the developed approach.